Strategi Pendidikan dalam Menumbuhkan Kemampuan Berfikir Kritis Anak Usia Dini di Masa Covid-19 - Azimatul Chusnah; Nur Alvi Inayati; Linda Puspita Sari; Imam Syafi’i (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
This study aims to describe and understand the strategy of educators in carrying out their duties during the COVID-19 pandemic in fostering critical thinking skills in early childhood. This research method uses qualitative research with a case study approach. Data collection techniques in this study using observation, interviews, and documentation. While the data analysis used the Miles and Huberman model with the stages of data reduction, data presentation, verification, and conclusion drawing. The results of this study indicate that, first, there is a change in the strategy for implementing the duties of teachers/educators, namely as planners and assessors of children's learning outcomes. While the task as implementers in early childhood educator learning in collaboration with teachers / educators at home, namely the child's parents. Second, the strategy of teachers/educators at home to cultivate children's critical thinking skills is to invite children to understand the reasons for schooling at home, the reasons for the obligation to use masks when leaving the house and others by using discussion and exemplary methods.